Inula graveolens induces selective cytotoxicity in glioblastoma and chronic leukemia cells - Koc,Kubra (2021)
SUMMARY OBJECTIVE: Crude oil extracts, components of extracts, and ethanolic extracts of Inula graveolens possess various pharmacological activities on various cancer cells including antioxidative and antiproliferative effects. Aqueous extract of this species has not been investigated on the liquid malignancies and solid tumors with a high incidence of treatment refractoriness and poor survival outcomes such as glioblastoma and leukemia. Hence, the present study aimed to evaluate the cytotoxic efficiency of I. graveolens aqueous extracts on human glioblastoma multiforme and chronic myelogenous leukemia cell lines in comparison to non-cancerous primary rat cerebral cortex and human peripheral blood mononuclear cells. METHODS: The cells were treated with the extracts of I. graveolens (125–1000 μg/mL) for 48 h, the cellular viability was identified using 3'-(4,5dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay, and lactate dehydrogenase release was measured to determine the cytotoxic potential. Total oxidant status and apurinic/apyrimidinic endodeoxyribonuclease 1 assays were used to determine the oxidative status of cells and DNA damage, respectively. RESULTS: I. graveolens showed selective cytotoxicity toward human glioblastoma multiforme and chronic myelogenous leukemia cell lines and exhibited a higher antiproliferative effect against cancer cells in comparison to non-cancerous cells. Moreover, it significantly reduced the apurinic/apyrimidinic endodeoxyribonuclease 1 levels on both cancer cell lines as compared with their control cells without changing the levels of an oxidative stress marker. CONCLUSION: The extracts of I. graveolens have anti-cancer potential on human glioblastoma multiforme and chronic myelogenous leukemia cell lines without causing oxidative stress.